A revision of the Thyropygus allevatus group. Part 2: the T. bifurcus subgroup (Diplopoda, Spirostreptida, Harpagophoridae) - Pimvichai, Piyatida; Enghoff, Henrik; Panha, Somsak (Zootaxa, 2009)
The Thyropygus bifurcus subgroup of the T. allevatus group is revised. Four new species are described from Thailand: T. demangei n. sp., T. quadricuspis n. sp., T. richardhoffmani n. sp., from Trang province and T. casjeekeli n. sp., from Krabi province. The other species of the T. bifurcus subgroup, viz., T. bifurcus (Demange, 1986), and T. enghoffi (Demange, 1989), are redescribed.